Fano resonant behaviour of waveguide mode in all-dielectric multilayer structure directly monitored by fluorescence of embedded dye molecules. (24th September 2019) - Kang, Byungjun; Motokura, Kengo; Fujii, Minoru; Nesterenko, Dmitry V; Sekkat, Zouheir; Hayashi, Shinji
Abstract: A method that allows direct monitoring of Fano resonant behaviours of local electric fields inside a waveguide layer in multilayer structures was developed. All-dielectric multilayer structures consisting of two polystyrene waveguide layers separated by a polyvinyl alcohol spacer layer were prepared. One of the waveguide layers was doped with fluorescent dye molecules. The fluorescence spectra of the sample were measured in a Kretschmann attenuated-total-reflection geometry as a function of the angle of incidence of the excitation light. The angle-scan fluorescence excitation spectra exhibited a sharp Fano line shape superposed on a broad band. Results of electromagnetic calculations of the electric field distribution inside the multilayer structure revealed that the local electric fields inside the dye-doped waveguide layer exhibit Fano resonant behaviours due to the near-field coupling to the waveguide mode supported by another waveguide layer. Using the calculated local electric fields, theoretical fluorescence spectra were calculated based on a point dipole model. The theoretical fluorescence spectra were found to reproduce the experimental ones very well, confirming that the observed Fano line shapes in the fluorescence spectra are the manifestation of the Fano resonant behaviours of the local electric fields inside the dye-doped layer.